Application of Transcriptomics to Compare the Carbohydrate Active Enzymes That Are Expressed by Diverse Genera of Anaerobic Fungi to Degrade Plant Cell Wall Carbohydrates - Gruninger, Robert J.; Nguyen, Thi T. M.; Reid, Ian D.; Yanke, Jay L.; Wang, Pan; Abbott, Denis W.; Tsang, Adrian; McAllister, Tim (Frontiers in Microbiology, 2018)
The efficiency with which the anaerobic fungi (phylum Neocallimastigomycota) degrade plant biomass is well recognized and in recent years has received renewed interest. To further understand the biological mechanisms that are utilized by the rumen anaerobic fungi to break down lignocellulose, we have used a transcriptomic approach to examine carbohydrate digestion by Neocallimastix frontalis, Piromyces rhizinflata, Orpinomyces joyonii, and Anaeromyces mucronatus cultured on several carbon sources. The number of predicted unique transcripts ranged from 6,633 to 12,751. Pfam domains were identified in 62%-70% of the fungal proteins and were linked to gene ontology terms to infer the biological function of the transcripts. Most of the predicted functions are consistent across species suggesting a similar overall strategy evolved for successful colonization of the rumen. However, the presence of differential profiles in enzyme classes suggests that there may be also be niche specialization. All fungal species were found to express an extensive array of transcripts encoding carbohydrate active enzymes (CAZymes) ranging from 8.3% - 11.3% of the transcriptome. CAZyme families involved in hemicellulose digestion were the most abundant across all four fungi. This study provides additional insight into how anaerobic fungi have evolved to become specialists at breaking down the plant cell wall in the complex and, strictly anaerobic rumen ecosystem.